2001
DOI: 10.1017/s0144686x01008479
|View full text |Cite
|
Sign up to set email alerts
|

Care services for frail older people in South Korea

Abstract: This paper examines the changed social circumstances of older people in South Korea and specifically the increased need for formal health and social services for those who are frail and have no informal carers. The article begins with a summary account of the country's exceptionally rapid demographic, economic and social transformations, which demonstrates a widening gap between the population's expectations and needs, and health and social service provision. It then examines the recently initiated and now bur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…A government's efforts to introduce social policies that meet people's changing needs often override its efforts to maintain a slow rate of social change. The status and roles of older people in a society depend to a large extent on the resources that they have (Sokolovsky 1990;Shank and Keith 1995 ;Ingersoll-Dayton and Saengtienchai 1999 ;Kendig et al 1999 ;Oldman and Quilgars 1999 ;Vo-Thanh-Xuan and Liamputtong Rice 2000;Keasberry 2001;Oh and Warnes 2001;La Grange and Lock 2002;Vo-Thanh-Xuan and Liamputtong 2003). Research by social gerontologists has shown that income security, changes to the retirement age, the support of family and friends and independent living are the main elements required for older people to enjoy a fulfilling life (Kilmartin 1989;Ginn 1991, 1993 ;Ginn and Arber 1998 ;Irwin 1999;Milne and Williams 2000).…”
Section: Introductionmentioning
confidence: 99%
“…A government's efforts to introduce social policies that meet people's changing needs often override its efforts to maintain a slow rate of social change. The status and roles of older people in a society depend to a large extent on the resources that they have (Sokolovsky 1990;Shank and Keith 1995 ;Ingersoll-Dayton and Saengtienchai 1999 ;Kendig et al 1999 ;Oldman and Quilgars 1999 ;Vo-Thanh-Xuan and Liamputtong Rice 2000;Keasberry 2001;Oh and Warnes 2001;La Grange and Lock 2002;Vo-Thanh-Xuan and Liamputtong 2003). Research by social gerontologists has shown that income security, changes to the retirement age, the support of family and friends and independent living are the main elements required for older people to enjoy a fulfilling life (Kilmartin 1989;Ginn 1991, 1993 ;Ginn and Arber 1998 ;Irwin 1999;Milne and Williams 2000).…”
Section: Introductionmentioning
confidence: 99%
“…They have no work, no skills, and no pensions, and will grow old in poverty [24]. Countries with social programs and pension plans in place will need to adapt these programs to serve more older people [25,26]. Therefore, social workers need new theories of ageing to explain the changes taking place in developing countries, and new plans for social change that fit the needs of an ageing world.…”
Section: Theoretical Perspectives and Literaturementioning
confidence: 99%
“…(Macionis 2001: 390) In their study of ageism in South Korea, Oh and Warnes (2001) argued that in addition to modernisation, industrialisation and a wholesale change in occupations and values as well as the spread of secondary and higher education, feminism has empowered Korean women to seek equal rights with men. • Industrial societies often consign older people to marginal participation in the economy because they lack the knowledge and training demanded in a fast-changing marketplace.…”
Section: Origins Of Ageismmentioning
confidence: 99%